2011
DOI: 10.1186/1471-2474-12-46
|View full text |Cite
|
Sign up to set email alerts
|

Closing-wedge high tibial osteotomy: survival and risk factor analysis at long-term follow up

Abstract: BackgroundClosing-wedge high tibial osteotomy (HTO) is successful for the treatment of medial osteoarthritis with varus malalignment. Preoperative risk factors for HTO failure are still controversial. The aim of this study was to elucidate the outcome and assess the influence of risk factors on long term HTO survival.Methods199 patients were retrospectively studied with a mean follow-up period of 9.6 years after HTO. HTO failure was defined as the need for conversion to TKA. Survival was analyzed with the Kapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
70
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 46 publications
1
70
2
7
Order By: Relevance
“…However, studies with longer-term follow-up have demonstrated a deterioration in patient-reported outcomes over time. [17][18][19][20][21][22][23][24] The aim of this study was to assess survival and functional outcome at ten years following lateral closing wedge HTO, and to examine the predictors of each of these outcomes.…”
mentioning
confidence: 99%
“…However, studies with longer-term follow-up have demonstrated a deterioration in patient-reported outcomes over time. [17][18][19][20][21][22][23][24] The aim of this study was to assess survival and functional outcome at ten years following lateral closing wedge HTO, and to examine the predictors of each of these outcomes.…”
mentioning
confidence: 99%
“…The 2 most commonly used methods for HTO are lateral closing wedge and medial opening wedge osteotomy. Both methods have shown improvement in knee pain and function (Naudie et al 1999, van Raaij et al 2008, Efe et al 2011, W-Dahl et al 2012). Nevertheless, some patients later require a second procedure, a total knee arthroplasty (Naudie et al 1999), depending on the degree of osteoarthritis, their level of pain and function, and the degree of correction achieved.…”
mentioning
confidence: 99%
“…For instance, in the study of Benzakour, in which 23 patients needed arthroplasty, he stated that revision was performed for 37 patients due to some reasons, such as the need for osteotomy, removal of implant, and infection (11). In the series of Efe et al (13), with 199 diseases and a mean followup time of 9.6 years, the number of cases with progression to arthroplasty was found to be 36. However, it was specified that different complications were observed in 38 patients (19%) when complications requiring reoperation, such as lack of healing in the tibia, were also involved.…”
Section: Discussionmentioning
confidence: 99%
“…Efe et al (13) reported the outcome of surgery to be excellent in 54 patients, good in 74 patients, moderate in 51 patients, and poor in 20 patients. Moreover, in the study of Giagounidis, 33% of patients were found to be very satisfied with the result of operation and 42.6% was satisfied, but 24.5% was dissatisfied (14).…”
Section: Discussionmentioning
confidence: 99%